Genetic Heterogeneity of Lymphangiogenesis in Different Mouse Strains - Regenfuß, Birgit (American Society for Investigative Pathology, 2010)
Lymphangiogenesis plays an important role in tumor metastasis, wound healing, and immune reactions, such as after organ transplantation. Furthermore, novel antilymphangiogenic drugs are moving into clinical medicine, but so far nothing is known about a potential genetic heterogeneity influencing lymphangiogenesis. Using the mouse cornea micropocket assay (VEGF-C) and the suture-induced corneal neovascularization model in different inbred and wild–derived mouse strains (Balb/cAnNCrl, C57BL/6NCrl, 129S1/SvImJ, SJL/JCrl, Cast/EiJ, FVB/NCrl), significant differences in the lymphangiogenic response were detected: the lymphvascularized area varied up to 1.9-fold in the micropocket assay and up to 1.7-fold in the suture-induced neovascularization model between the “low-responder” strain BALB/c and the “high-responder” strain FVB in response to the same stimulus. Furthermore, the number of physiological lymphatic vascular extensions into the marginal zone of the normally alymphatic cornea in untreated eyes again showed a difference of 1.6-fold between low- and high-responders. An anti-inflammatory (prednisolone acetate) and a specific anti(lymph)angiogenic therapy (blocking anti–VEGFR-3 antibody) had different effects on the lymphvascularized area in BALB/c mice and FVB mice, suggesting a different responsiveness to antilymphangiogenic treatments. These data for the first time demonstrate significant differences in the lymphangiogenic response of several mouse strains and suggest underlying genetic factors influencing the lymphangiogenic response. These considerations need to be taken into account when using different mouse strains to study lymphangiogenesis and may also explain different success of antilymphangiogenic treatments in tumor patients.